The SCR of NO with CH4 over Co-, Co,Pt-, and H-mordenite catalysts - Lónyi, F. (2007)
The catalytic reduction of NO with methane was studied operando in the presence and absence of oxygen in the reaction mixture over Co-, Co,Pt-, and H-mordenite (CoM, CoPtM, HM) catalysts using the coupled methods of diffuse reflectance infrared Fourier-transform spectroscopy and mass spectroscopy (Operando-DRIFTS-MS). The reaction temperature was in the 573-773 K range, and the GHSV for nitric oxide was varied between 6000 and 60,000 h-1. In general, the Co-containing mordenite catalysts were more active than the HM. Over each catalyst two major surface intermediates were identified such as nitrosonium ion (NO+) and ammonia. The NO+ cations were shown to balance the negative charge on the zeolite framework. The NH3 molecules were bound either coordinately to Lewis-acid site Co2+ ions or were protonated on Brønsted acid sites and retained by the zeolite as NH4 + cations. The prevailing route of N2 formation was found to involve the reaction of NO+ and NH3 or NH4 + surface species. It was shown that the surface concentration of the intermediate ammonia governed the rate of NO conversion. If O2 was present in the feed gas it competed with the NO in the oxidation of methane and the surface intermediate ammonia. As a result, the steady-state concentration of the ammonia intermediate and the overall NO conversion to N2 decreased. Additional routes of N2 formation were revealed over the CoM and CoPtM catalysts. The cobalt facilitated the formation of NO+ and surface nitrate (NO3 -). Also nitrile (CN) and isocyanate (NCO) surface species were detected. The NO3 - could be rapidly reduced by methane to intermediate NH3 and, thereby, it increased the rate of NO conversion significantly. Nitrogen forming reactions can pass also through CN and NCO intermediates; however, the share of these reaction routes in the overall N2 generation process was minor.